ANALYSIS OF THE CONTRIBUTION OF WORKLOAD, CAREER DEVELOPMENT, AND MOTIVATION TO TEACHER PRODUCTIVITY: EMPIRICAL EVIDENCE FROM PRIVATE EDUCATION INSTITUTIONS IN INDONESIA - Rosidi, Imron; Rozi, Fahrul; Young, Felina C. (Dynamic Management Journal, 2025)
This study aims to analyze the influence of workload, career development, and motivation on teacher productivity at the Aditya Karya Education Foundation. This research is important because teacher productivity is a key factor in improving the quality of education, but there are still few studies that comprehensively examine these factors in private educational institutions. This quantitative research involved 100 teacher respondents with a double linear regression analysis method using SPSS. The results show that workload, career development, and motivation significantly affect teacher productivity, both partially and simultaneously. The novelty of this research lies in a holistic approach in identifying the determinants of teacher productivity in the educational foundation environment, which can be a reference for school management in designing human resource development policies. The contribution of this research provides practical recommendations to improve teacher performance through workload optimization, career development programs, and providing the right motivation. These findings also enrich the education management literature with empirical evidence from local contexts. Keywords: Workload, Career Development, Motivation, Productivity.